Now is the Psychological Moment' Earle Page and the Imagining of Australia - Wilks, Stephen (ANU Press, 2020)
Earle Christmas Grafton Page (1880-1961) - surgeon, Country Party leader, treasurer and prime minister - was perhaps the most extraordinary visionary to hold high public office in twentieth-century Australia. Over decades, he made determined efforts to seize 'the psychological moment', and thereby realise his vision of a decentralised, regionalised and rationally ordered nation. Page's unique dreaming of a very different Australia encompassed new states, hydroelectricity, economic planning, cooperative federalism and rural universities. His story casts light on the wider place in history of visions of national development. He was Australia's most important advocate of developmentalism, the important yet little-studied stream of thought that assumes that governments can lead the nation to realise its economic potential. His audacious synthesis of ideas delineated and stretched the Australian political imagination. Page's rich career confirms that Australia has long inspired popular ideals of national development, but also suggests that their practical implementation was increasingly challenged during the twentieth century. Effervescent, intelligent and somewhat eccentric, Page was one of Australia's great optimists. Few Australian leaders who stood for so much have since been so neglected.